2011
DOI: 10.1128/jvi.02541-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivities of Retroviruses to Integrase Strand Transfer Inhibitors

Abstract: Integrase inhibitors are emerging anti-human immunodeficiency virus (HIV) drugs, and multiple retroviruses and transposable elements were evaluated here for susceptibilities to raltegravir (RAL) and elvitegravir (EVG). All viruses, including primate and nonprimate lentiviruses, a Betaretrovirus, a Gammaretrovirus, and the Alpharetrovirus Rous sarcoma virus (RSV), were susceptible to inhibition by RAL. EVG potently inhibited all lentiviruses and intermediately inhibited Betaretrovirus and Gammaretrovirus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…We next evaluated the inhibitory effect of RAL, the first INSTI approved for clinical use, on SRV-4 infection. RAL has potent anti-HIV-1 activity in addition to a broad antiviral spectrum including simian immunodeficiency virus (SIV) (33), MLV (34), XMRV (11), and SRV-3 (19). We also observed that RAL inhibited HIV-1 and MoMLV infections (Table 1).…”
Section: Inhibitory Effect Of Hiv-1 Nnrtis On Srv-4 Infectionmentioning
confidence: 73%
See 2 more Smart Citations
“…We next evaluated the inhibitory effect of RAL, the first INSTI approved for clinical use, on SRV-4 infection. RAL has potent anti-HIV-1 activity in addition to a broad antiviral spectrum including simian immunodeficiency virus (SIV) (33), MLV (34), XMRV (11), and SRV-3 (19). We also observed that RAL inhibited HIV-1 and MoMLV infections (Table 1).…”
Section: Inhibitory Effect Of Hiv-1 Nnrtis On Srv-4 Infectionmentioning
confidence: 73%
“…Reportedly, SRV-3 also contains amino acids corresponding to N155H and F121Y, which are other INSTI resistance mutations; however, SRV-3 shows complete susceptibility to RAL (19). In contrast, bovine immunodeficiency virus (BIV) reportedly showed 23-fold resistance to RAL compared to wild-type HIV-1, although BIV contains a histidine (H) residue at the position corresponding to N155 (19), as seen in SRV-4, indicating that N155H is not a determinant of RAL susceptibility in retroviruses other than HIV. Although in the present study, FIV showed less susceptibility to RAL than the other retroviruses/lentiviruses tested (Table 1), FIV does not contain major INSTI resistance mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a negative control, viruses were heat inactivated at 56°C for 1 h, and 100 M AZT was added to the target cells throughout the experiment. As an additional control, one subset of infected cells was treated with 1 M (10ϫ the reported 95% effective concentration [EC 95 ]) raltegravir, an active-site inhibitor of retroviral integrases (41,42). The infection levels achieved for the experimental and control assays are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7, blue). INSTIs display generally broad-spectrum antiretroviral activity (56,205,206), and co-crystallization with the PFV CI accordingly revealed critical aspects of the mechanism of INSTI action (94,207,208). As predicted from prior solution-based measures (201), the co-planar oxygen atoms engage the divalent metal ions at the integrase active site.…”
Section: Integrase Strand Transfer Inhibitors (Instis)mentioning
confidence: 90%